Tunable Aryl Alkyl Ionic Liquids with Weakly Coordinating Tetrakis((1, 1, 1, 3, 3, 3‐hexafluoropropan‐2‐yl)oxy)borate [B(hfip)4] Anions. Issue 29 (22nd June 2016) - Kaliner, Maria; Rupp, Alexander; Krossing, Ingo; Strassner, Thomas
Abstract: Weakly coordinating borate or aluminate anions have recently been shown to yield interesting properties of the resulting ionic liquids (ILs). The same is true for large phenyl‐substituted imidazolium cations, which can be tuned by the choice, position, or number of substituents on the aromatic ring. We were therefore interested to combine these aryl alkyl imidazolium cations with the weakly coordinating tetrakis((1, 1, 1, 3, 3, 3‐hexafluoropropan‐2‐yl)oxy)borate [B(hfip)4 ] − anions to study the physical properties and viscosities of these ionic liquids. Despite the large size and high molecular weight of these readily available ILs, they are liquid at room temperature and show remarkably low glass transition points and relatively high decomposition temperatures. Abstract : Bulky TAAILs : Combining weakly coordinating bulky tetrakis((1, 1, 1, 3, 3, 3‐hexafluoropropan‐2‐yl)oxy)borate [B(hfip)4 ] − anions with aryl alkyl imidazolium cations results in tunable alkyl aryl ionic liquids (TAAILs; see figure) that show remarkably low melting points despite of their large size and high molecular weight. These TAAILs are liquid at room temperature.